2021
DOI: 10.1140/epjc/s10052-021-09867-2
|View full text |Cite
|
Sign up to set email alerts
|

Masses and strong decays of open charm hexaquark states $$\Sigma _{c}^{(*)}{\Sigma }_{c}^{(*)}$$

Abstract: Inspired by the recent discovery of the doubly charmed tetraquark state $$T_{cc}^{+}$$ T cc + by the LHCb Collaboration, we perform a systematic study of masses and strong decays of open charm hexaquark states $${\Sigma }_{c}^{(*)}\Sigma _{c}^{(*)}$$ Σ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…The existence of the molecular states in the c c system is solid and supported by many literatures [83,85,102,104,105,108,109]. These literatures all suggested the existence of the molecular state [ c c ] 0 0 , while for the existence of [ c c ] 1 1 molecule, the conclusion still relied on the different treatments of theoretical models.…”
Section: T CC State and Other Heavy Flavor Molecular Statesmentioning
confidence: 88%
“…The existence of the molecular states in the c c system is solid and supported by many literatures [83,85,102,104,105,108,109]. These literatures all suggested the existence of the molecular state [ c c ] 0 0 , while for the existence of [ c c ] 1 1 molecule, the conclusion still relied on the different treatments of theoretical models.…”
Section: T CC State and Other Heavy Flavor Molecular Statesmentioning
confidence: 88%
“…[1131], the authors found that the isoscalar Λ c Λc , Σ ( * ) c Σ( * ) c and isovector Λ c Σ( * ) c as well as their doubly charmed and doubly bottom counterparts are good candidates of the molecular hexaquarks. The calculations in various models [1132,581,1133,1134,1135,268,342,276,1136,1137,1138] In Ref. [393], the authors proposed an alternative way to determine the spins of the P c (4440) and P c (4457) from the spectrum of the Ξ ( * ) cc Σ ( * ) c systems with the help of lattice QCD [1140].…”
Section: Nξ ( * ) CC Systemsmentioning
confidence: 99%
“…The di-baryon systems that are composed of two charmed baryons are more likely to be bound, since the large reduced mass can facilitate the stabilization of such systems. As the heavy flavor siblings of the nucleon, the molecular states in the Σ c Σ c system have been investigated in a series of works [79][80][81][82][83][84][85]. In this work, we will mainly concentrate on the interactions of the Σ c Σ c system, and explore the relevance of intermediate states in the two-pion exchange (TPE) loops within the chiral effective field theory (χEFT).…”
Section: Introductionmentioning
confidence: 99%